A Political Economy Of The Middle East - RICHARDS, Alan (Westview, 2008)
This integrated, analytic text presents a comprehensive analysis of the transformation of the political economy of development in the contemporary Middle East over the past several decades. Extensively rewritten and revised, the third edition of A Political Economy of the Middle East retains a focus on the interaction of economic development processes, state systems, and social actors even as it also: Documents the many changes in demography, education, labor markets, urbanization, water and agriculture, and international labor migration in the Middle East in recent years; Considers the effect of rising oil prices on reinforcement of authoritarian governance in the region; Refines its assessment of â€œthe Washington Consensusâ€ to provide a more nuanced approach to the issue of the shifting balance of state and market in economic growth and reform (in an entirely rewritten Chapter 9); Presents Islamism as a vital force in the region that is nonetheless a vast, diverse social movement with many conflicting participants (in a wholly revised Chapter 14).